2016
DOI: 10.1002/chem.201504970
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the Concept of Nonlinear Effects in Catalytic Reactions Beyond Asymmetric Catalysis

Abstract: The observation and investigation of nonlinear effects in catalytic reactions provides valuable mechanistic insight. However, the applicability of this method was, until now, limited to molecules possessing chirality and therefore to asymmetric synthesis. The concept of nonlinear effects is expanded to catalytic reactions beyond asymmetric catalysis by using derivatives instead of enantiomers and by considering rates instead of enantiomeric excess. Additionally, its systematic application to investigate the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…However, an unexpected NLE on the P:H ratio outcome was observed (Figure 1C). 11 As the enantiomeric ratio of 2b decreases, the P:H ratio erodes. This NLE could be explained with two reasonable possible scenarios (Figure 1D):…”
Section: Resultsmentioning
confidence: 99%
“…However, an unexpected NLE on the P:H ratio outcome was observed (Figure 1C). 11 As the enantiomeric ratio of 2b decreases, the P:H ratio erodes. This NLE could be explained with two reasonable possible scenarios (Figure 1D):…”
Section: Resultsmentioning
confidence: 99%
“…The first example from literature to be investigated is the Rh-catalyzed direct C-H amination of 2-phenylpyridines using organic azides (Scheme 3). 16 Scheme 3. Rh(III)-catalyzed direct C-H amination of 2-phenylpyridines with organic azides.…”
Section: Complexity A(t)-profile [A 0 -P(t)]-profile Catalyst Deactivmentioning
confidence: 99%
“…The authors performed detailed experimental and computational mechanistic studies and concluded that the TDTS is most likely one of the transition states leading to the postulated Rh(V) -nitrenoid intermediate, rather than the TS of C-H activation of 2-phenylpyridine. 16 Based on initial rate experiments, the kinetic model shown in Scheme 3b was proposed. 16 The TDI was suggested to be distributed between species 1 and 2, with complex 1 being predominant (Scheme 3).…”
Section: Complexity A(t)-profile [A 0 -P(t)]-profile Catalyst Deactivmentioning
confidence: 99%
See 2 more Smart Citations